Self-repairing of rock cracks by microbially induced silicate precipitation - Ryo Uenishi; Ibuki Nishimura; Hitoshi Matsubara (International Journal of Geo-Engineering)
Abstract The natural silicate minerals with a ring structure were observed on a tuff breccia outcrop in Okinawa, Japan, appearing to self-repair cracks. Generally, silicate minerals are difficult to dissolve in water and their mechanical strength is relatively higher than that of other natural precipitated minerals, such as carbonate minerals. Therefore, if this natural phenomenon is induced by the microbial activities and can be artificially replicated, it could offer a self-organized geo-improvement technology characterized by insolubility and durability. In this study, the authors determined that this mineral has 26–50% rock mass quality (Q value) and 63–71% surface hardness (L value) compared to the host rock, and its growth rate is 1.21 mm/year. Therefore, this mineral is considered to have a crack repair function as it grows. According to observations by scanning electron microscope, many microorganisms were confirmed to be present in the minerals, and genera of Actinobacteria, Proteobacteria, Cyanobacteria, and others were detected by 16S rRNA analysis. Additionally, experiments using these microorganisms revealed that photoautotrophs and other microbial communities are deeply involved in the production of silicate minerals. These results significantly enhance the potential for developing a silicate-based self-healing technology for weathered and/or cracked rock in nature.